"They're My Go-To People": A Qualitative Study of Support Networks for People Recently Diagnosed With HIV in Queensland, Australia. (8th November 2022) - Hollingdrake, Olivia; Lui, Chi-Wai; Dean, Judith A.; Mutch, Allyson; Howard, Chris; Fitzgerald, Lisa
Abstract: Support networks promote care engagement and prevent social isolation for people living with HIV (PLWH). This study examined the personal support networks of recently diagnosed PLWH and explored how these networks change over time. We developed qualitative social network maps with 10 recently diagnosed PLWH in Queensland and identified unique and dynamic support networks. Network changes over time were influenced by changing support needs and experiences of stigma. Some support networks grew, whereas others remained small and close-knit or became sparse. The pivotal role of peers for information and emotional support was revealed. Socially isolated PLWH also described substantial reliance on long-term professional support. Others described reasons why health professionals were excluded from support networks, revealing the importance of nonjudgmental attitudes and HIV literacy among health professionals. Facilitating ongoing links with peers and professionals are crucial strategies to help PLWH foster effective and sustainable networks for comprehensive long-term support.